2006
DOI: 10.1016/j.jadohealth.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Traffic Offenses from Adolescent Licensure into Early Young Adulthood

Abstract: Purpose-This article examines adolescent psychosocial and problem behavior characteristics as predictors of traffic offenses from licensure to early young adulthood.Methods-Data for this study were from a school-based sample that was surveyed in 10th and 12th grades, and again in early young adulthood. In addition, state driver history records were obtained for each participant in the study and provided a complete traffic offense history.Results-Models adjusted for driving exposure showed varying patterns of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Teen drivers' intentions to violate driving rules are less when parental supervision is greater (Desrichard et al, 2007). Also, greater parental monitoring during adolescence has been shown to predict safer young adult driving outcomes, including less high-risk driving behavior and fewer traffi c offenses and crashes (Bingham and Shope, 2004a,b;Bingham et al, 2005Bingham et al, , 2006. The addition of preventing drinking and driving as one of the specifi c objectives of parent-directed interventions may hold promise as a means of reducing teen crash risk, not only in the early stages of driving but also potentially for years to come Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Teen drivers' intentions to violate driving rules are less when parental supervision is greater (Desrichard et al, 2007). Also, greater parental monitoring during adolescence has been shown to predict safer young adult driving outcomes, including less high-risk driving behavior and fewer traffi c offenses and crashes (Bingham and Shope, 2004a,b;Bingham et al, 2005Bingham et al, , 2006. The addition of preventing drinking and driving as one of the specifi c objectives of parent-directed interventions may hold promise as a means of reducing teen crash risk, not only in the early stages of driving but also potentially for years to come Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, the analyses did not control for the teenager's substance use. Bingham et al (2006) found that high parental monitoring during high school was protective against alcohol-related offenses at ages 20-24 for men, but not women, and not at age 19. These fi ndings suggest that parenting practices, such as parental monitoring, might be associated with lower rates of DWI.…”
mentioning
confidence: 89%
“…These fi ndings suggest that parenting practices, such as parental monitoring, might be associated with lower rates of DWI. Although parents could exert direct effects on teenage DWI and RWI, as purported with a teenage-to-young-adult cohort (Bingham et al, 2006), much of their effect is likely to be indirect through their concerns and efforts to discourage their teenage children from drinking or other substance use. In a regional administration of the Youth Risk Behavior Survey, parental support was related to DWI but not RWI, and effects were reduced to nonsignifi cance after accounting for the teenager's substance use behaviors (Sabel et al, 2004).…”
Section: Factors Associated With Teenage Dwi and Rwimentioning
confidence: 99%
“…Studies using the problem behaviour approach have shown that problem behaviour in traffic is highly related to other problem behaviours such as cigarette smoking, alcohol misuse, marijuana use, social maladjustment and poor school performance (Bingham et al, 2006;Bingham and Shope, 2004a, b). These findings are in accordance with the Problem Behaviour Theory, which distinguishes between behaviour that is approved of by the general society and problem behaviour that is condemned.…”
Section: Introductionmentioning
confidence: 99%